2007
DOI: 10.1038/sj.bmt.1705588
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal thrombotic microangiopathy induced by FK506 in rats

Abstract: Thrombotic microangiopathy (TMA) is one of the severe complications after stem cell transplantation (SCT) and is associated with graft-versus-host disease (GVHD) prophylaxis including FK506. In this study, we experimented on rats using FK506 to demonstrate the occurrence of intestinal TMA. FK506 was administrated into Wistar/ ST rats intraperitoneally for 7 days. Rats were examined histopathologically after FK506 injection using light and electron microscopy and immunohistochemistry. FK506 concentrations in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…In addition, we recently established a rat model of intestinal microangiopathy induced by tacrolimus alone. 25 The pathology was consistent with human i-TAM after allo-HSCT, and rats recovered from microangiopathy after withdrawal of tacrolimus. Therefore, we hypothesized that 'not intensified' strategy for i-TAM would minimize drug-induced endothelial damage and improve outcome, and divided patients into four groups according to the way of immunosuppressant use.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, we recently established a rat model of intestinal microangiopathy induced by tacrolimus alone. 25 The pathology was consistent with human i-TAM after allo-HSCT, and rats recovered from microangiopathy after withdrawal of tacrolimus. Therefore, we hypothesized that 'not intensified' strategy for i-TAM would minimize drug-induced endothelial damage and improve outcome, and divided patients into four groups according to the way of immunosuppressant use.…”
Section: Discussionmentioning
confidence: 79%
“…The addition of mPSL to Tac and sMTX strongly suppressed acute GVHD in unrelated donor BMT but not chronic GVHD [35]. It has been suggested that calcineurin inhibitors are involved in the development of intestinal thrombotic microangiopathy, a life-threatening complication after allogeneic transplantation, in humans and rats [38][39][40]. The blood concentration of Tac was not necessarily high in patients who developed Tac-related encephalopathy [41].…”
Section: Tacrolimus (Tac)-based Regimensmentioning
confidence: 94%
“…Клиническая картина дан-ного осложнения зависит от органа-мишени. Описаны развитие перикардита, поражение почек в виде гемо-литико-уремического синдрома (ГУС), головного моз-га и кишечника [1][2][3]. Зачастую ТА-ТМА может про-текать под «маской» других состояний, вызванных токсичностью препаратов и характерных для раннего посттрансплантационного периода, таких как замед-ленное восстановление гемопоэза, инфекционные осложнения, реакция «трансплантат против хозяина» (РТПХ), дисфункция почек и неврологические нару-шения [4].…”
Section: актуальностьunclassified